Comparative study of Alvarado score and RIPASA score in the diagnosis of acute appendicitis - Chavan, Shahaji; Bhatnagar, Shubhi; Bendre, Mahendra; Sinha, Nilesh (International Surgery Journal, 2018)
Background: Acute appendicitis despite being a common problem, remains a difficult diagnosis to establish. A delay to diagnose this condition as well as negative appendicectomies should be prevented. The above problems can be avoided by using scoring systems. This study aims to compare the efficacy of Alvarado score and RIPASA score in the diagnosis of acute appendicitis. Methods: In this study, 100 cases of appendicitis were admitted. Alvarado and RIPASA scores were applied to all patients. The scores were compared with post-operative histopathology findings. Results: Alvarado score was positive in 75% cases and RIPASA score was present in 90% cases. Histologically, appendicitis was present in 99% cases. Conclusions: RIPASA score is more efficient in diagnosing acute appendicitis compared to Alvarado score.